2000
DOI: 10.1266/ggs.75.79
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation and structural conservation in the D-loop region and flanking genes of mitochondrial DNA from Japanese pond frogs.

Abstract: The nucleotide sequences of the D-loop region and its flanking genes of the mitochondrial DNA (mtDNA) from Japanese pond frogs were determined by the methods of PCR, cloning, and sequencing. The frogs belonged to two species, one subspecies, and one local race. The gene arrangements adjacent to the D-loop region were analyzed. The frogs shared a unique mitochondrial gene order that was found in Rana catesbeiana; i.e., cyt b -D-loop region -tRNA Leu(CUN) -tRNA Thr -tRNA Pro -tRNA Phe -12S rRNA. The arrangements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
1
20
0
Order By: Relevance
“…The repetitive segment (757 bp) consisted of 40 copies of a 16-bp sequence, 3 copies of a 22-bp sequence, and 3 copies of a 17-bp sequence. The same types of large repetitive segments (600 bp ~ 1200 bp) have been reported in the sibling species R. porosa (Sumida et al, 2000b). Differences in the numbers of copies of tandem repeats caused large length variations in the D-loop regions of individual Japanese pond frogs within the R. nigromaculata group (Sumida et al, 2000b).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The repetitive segment (757 bp) consisted of 40 copies of a 16-bp sequence, 3 copies of a 22-bp sequence, and 3 copies of a 17-bp sequence. The same types of large repetitive segments (600 bp ~ 1200 bp) have been reported in the sibling species R. porosa (Sumida et al, 2000b). Differences in the numbers of copies of tandem repeats caused large length variations in the D-loop regions of individual Japanese pond frogs within the R. nigromaculata group (Sumida et al, 2000b).…”
Section: Resultssupporting
confidence: 58%
“…The complete sequence of the mitochondrial DNA genome has been determined in only two species Xenopus laevis (Roe et al, 1985) and Typhlonectes natans (Zardoya and Meyer, 2000) among amphibians, whereas partial sequences including multiple gene region of the mtDNA genome have been reported in several amphibian species (Yoneyama, 1987;Yang et al, 1994;Shaffer and McKnight, 1996;Macey et al, 1997;Feller and Hedges, 1998;Sumida et al, 1998Sumida et al, , 2000aMacey et al, 2001). Xenopus shares the conserved vertebrate gene order, whereas several Rana species include gene rearrangements in partial sequences between the control region and the 12S rRNA gene (Sumida et al, 2000b). The present study showed the whole aspects of the mitochondrial gene rearrangements in the Japanese pond frog R. nigromaculata.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tRNA cluster upstream of the 12S rRNA gene was also identified in the Japanese pond frog, Rana nigromaculata (Sumida et al, 2001) (Fig. 3) and other known ranid frogs (Yoneyama, 1987;Macey et al, 1997;Sumida et al, 2000). However, the rearrangement of the ND5 gene has not been seen in other amphibians sequenced previously.…”
Section: Resultsmentioning
confidence: 69%
“…For the population genetic part of our study, we developed variants of universal primers that succeeded amplifying a large part of the moderately variable cytochrome b gene in Mantella. Attempts of amplifying and sequencing the presumably more variable control region in Mantella were unsuccessful, probably because ranoid frogs can be characterised by important length polymorphisms of this gene (Sumida et al, 2000) and by a genomic rearrangement that led to the absence of conservative priming sites between the cytochrome b and control region genes (Macey et al, 1997;Sumida et al, 2000Sumida et al, , 2001.…”
Section: Dna Sequencingmentioning
confidence: 99%